Early detection of developmental dysplasia of hip by ultrasound. Issue 3 (May 2021) - Gyurkovits, Zita; Sohár, Gellért; Baricsa, Anna; Németh, Gábor; Orvos, Hajnalka; Dubs, Beat
Objective: To assess the effectiveness of early universal ultrasound (US) screening of developmental dysplasia of the hip (DDH). Study design: A prospective study of universal hip screening of all mature neonates was conducted from 2012 to 2013, at the Department of Obstetrics and Gynaecology, University of Szeged; 1636 newborns (3272 hips) had clinical examinations and hip ultrasound by the Graf method within the1st 3 days of life. Prevalence of DDH, risk factors, sensitivity and specificity of clinical examinations were evaluated. Results: At the 1st US, 70 of the examined 3272 hips (2.14%) were found to be positive. According to Graf categories, the following distribution was observed: type II C, 21 hips (30.0%); D, 24 hips (34.28%); III, 24 hips (34.28%); IV, 1 hip (1.44%). Regarding the risk factors, female gender, breech presentation and positive family history proved to be significant. Interestingly, 28 (50.90%) of the 55 newborns with DDH had neither positive physical signs nor any risk factors, except being female. The physical examination was calculated for sensitivity (20.0%) and specificity (98.34%). Conclusions: In our 1-year period study, 50.9% of the newborns with DDH had neither any positive physical signs nor any risk factors, except being a female. In contrast, early universal US screening of the hip facilitated to diagnose all cases with hip dysplasia. Hip sonography is an effective mode of prevention in orthopaedics, however further studies are needed to compare the rates of operative procedures in selective versus universal screening models.